Prospects and Potential For Developing Halal Tourism In Sambas District As A Border Area Of Indonesia – Malaysia - Oskar Hutagaluh; Muslimin H Kara; Abdul Wahid Haddade; Sumar’in (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research aims to identify the potential and prospects for the development of halal tourism in Sambas Regency, a strategic border area between Indonesia and Malaysia. The research method used is descriptive qualitative through field data collection and in-depth analysis of various aspects supporting halal tourism, such as culture, natural resources, and government policies. The research results indicate that Sambas Regency has great potential to develop into a leading halal tourism destination due to its diverse Islamic culture, strategic geographical position, and commitment from the local government. However, the research also revealed constraints in the form of limited infrastructure and human resources that need to be improved. This research implies the need for integrated and innovative policies in developing halal tourism in Sambas Regency to enhance competitiveness at the national and international levels and to encourage local economic growth.